Osteoid Osteoma of the Basilar Border of the Mandible: A Diagnostic Dilemma - Rym Kammoun; Imen Chaabani; Sonia Ghoul; Touhami Ben Alaya (Case Reports in Dentistry)
Introduction. Osteoid osteoma is a benign osseous tumor characterized by an excessive formation of unmineralized bone matrix. The aim of this study was to present, through a case report, the clinical and radiological manifestations of osteoid osteoma affecting the left basilar border of the mandible. Observation. A 30-year-old male patient presented with left mandibular pain of unknown etiology. The chief complaint was mandibular pain accentuating mainly at night, originating in the left basilar border, and radiating to the whole mandibular hemi-arch. Extraoral examination revealed a small, bone-consistent, and slightly painful swelling. Computed tomography scan revealed a well-limited, infracentimetric, and mixed osteolytic image with central nidus and peripheral osteocondensation. Histological examination revealed osteoid osteoma. Surgical excision of the lesion was performed, and the pain stopped immediately. Discussion. This benign tumor presents many clinical and radiological features similar to other lesions. To differentiate osteoid osteoma from these other bone pathoses, practitioners should have a clear concept and keen observation skills. Confrontation of the clinical, radiological, and anatomopathological data is therefore essential to establish the correct diagnosis and to determine the appropriate treatment plan.